THE EFFECT OF DICTOGLOSS STRATEGY ON THE STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT AT MTsN 1 MEDAN - Fajrin Ritonga, Khairuna (Faculty of Tarbiyah nad Teacher Training, 2021)
The objective of this research is to find out whether or not there is significant effect of Dictogloss strategy on students’ writing ability in narrative text at ninth grade students’ of MTsN 1 Medan. This research is quantitative research with quasi experimental design. This research was carried out in the ninth grade students of MTsN 1 Medan academic year 2020/2021. The total number of population was 426 students, and the researcher took 37 students for experimental class and 36 students for control class, which means 73 students as total of the sample. To collecting data in this research, the researcher used written tests as the instrument. The tests were pre-test was given before the treatment and post-test which was given after the treatment. The data in this research obtained were analyzed by using t-test with 5% (0,05) significance level. Furthermore, the researcher found that the mean score of post-test in experimental class was higher than the mean score of post test in control class (77,92>71,11). The t-test result also presents that t0 (4,434) was higher than ttable in the significance level 5% (0,05) with the degree of freedom 71 is 1,667. Therefore, t0 result >ttable generated that H0 (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted. The calculation of effect size was 1,04 which in the range of effect criteria included to strong effect. It means, Dictogloss strategy has significant effect on the students’ writing ability in narrative text at ninth grade students of MTsN 1 Medan